Reformulation and Priorities for Reducing Energy Density; Results from a Cross-Sectional Survey on Fat Content in Pre-Packed Cakes and Biscuits Sold in British Supermarkets - Alessandrini, Roberta (Nutrients, 2019)
Cakes and biscuits contribute to energy, total and saturated fat and sugar in British diets. So far, the UK government has prompted manufacturers to reduce energy density in these products through a reduction of their sugar content. We conducted a cross-sectional survey of the fat content of cakes and biscuits available in nine UK supermarket chains. In cakes (n = 381), the mean total fat content was 17.9 ± 5.2 g/100 g (39% of the overall energy); range (1.4–35.6 g/100 g) and the average saturated fat content in cakes was 5.9 ± 3.4 g/100 g (13% of the overall energy); range (0.3–20 g/100 g). In biscuits (n = 481), the mean total fat content was 21.8 g ± 6.3 g/100 g (40% of the overall energy); range (0.7–38.9 g/100 g) and the average saturated fat content was 11.4 ± 4.9 g/100 g (23% of the overall energy); range (0.3–22.3 g/100 g). In both cakes and biscuits, total and saturated fat content was positively correlated with energy density. Our results show that cakes and biscuits sold in UK supermarkets are high in total and saturated fat, and that fat content contributes substantially to product energy density. Fat reformulation in these products would effectively reduce energy density, calorie intake and help prevent obesity. Fat reformulation should be implemented simultaneously with sugar reformulation and be focused on saturated fat, as this will have the additional effect of lowering LDL cholesterol.